Ngeneng Ngening: Local Traditions in Dealing with Covid19 (Study on The Balinese Age Community of Bayung Gede Village) - Lamopia, I Wayan Gede; Wulandari, Riza (Nusantara Science and Technology Proceedings)
The purpose of this study is to elaborate on the tradition of Ngeneng Ngening ceremonies conducted by the Balinese Age Community of Bayung Gede Village and also look at the religious, social, and ecological impacts and Ngeneng-Ngening. Research using qualitative methods is selected to help solve this problem. The theory used in this research on ngeneng ngening is Talcot Parson's Structural Functionalism with 4 indicators namely Adaptation, Goal, Integration, and Latency. Based on the results on the ground it was found that the application of this ngeneng ngening tradition refers to the rules of PHDI and the Bali Customary Village Assembly. The implementation process in Bayung Gede Village is carried out for 3 days where all levels of society are at home, working at home and moving from home. People are prohibited from wewidangan activities ranging from receiving guests or visiting. Nunas Ica Ngeneng Ngening is carried out at the time of tilem kedasa, which is only allowed to do nunas ica and earth brew activities and prepare banten rayunan and yellow white sodaan for Sanggah Kamulan, banten segehan white yellow in natar merajan and various other networks to ngaturang bakti to bhatara kawitan and Sang Hyang Widhi Wasa.